USALITY RELATIONS IN LEGAL JUDGMENTS ON THE EXAMPLE OF THE EUROPEAN COURT OF HUMAN RIGTHS - STRĘBSKA, Katarzyna (Comparative Legilinguistics, 2013)
The aim of the paper is to analyze the judgment as a legal genre whereby causality relations behave in a particular way depending on the type of the connective used. The relations of causality are described against a background of interactional linguistics, semantic and lexical vagueness as well as the degree of subjectivity in the selected types of causality. The emphasis in the present analysis is on the epistemic causality as the one most closely related to the judicial discourse and the language of law. In this type of causality it is the author who becomes the source of a logical continuum between the cause and effect as opposed to the other extremity where the source is outside the speaker. The analysed corpus consists of 20 judgments of the European Court of Human Rights (altogether 496 sentences have been identified where particular causal connectives were present) issued between 2007 and 2013 and available at the official site of the court: http://www.echr.coe.int/ECHR/homepage_en. The judgments have been selected in order to identify and conduct a quantitative and qualitative analysis of the relation of causality as realized by three English causal connectives: because, as and therefore.